Identifikasi Jenis Bakteri Pada Layar Handphone Mahasiswa Pendidikan Biologi dan Pemanfaatannya Sebagai Media Pembelajaran - Nabila, Putri; Kundera, I Nengah; Windarsih, Yulia; Sutrisnawati, Sutrisnawati; Budiarsa, I Made; Ashari, Abdul (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This research aimed to isolate and identify the types of bacteria present on the surface of biology education students' mobile phone screens. This was an exploratory study using a bacterial isolation method.Bacteria found on the mobile phone screens were cultivated using MacConkey agar, a selective medium specifically designed to detect and identify Gram-negative bacteria, particularly Enterobacteriaceae like Escherichia coli. The accuracy of the Escherichia coli data from the phone screen samples, after processing with the Microbact System, was 96.39%.Malt Extract Agar (MEA) was also used as a selective medium to detect and identify Gram-positive fungi, such as Candida albicans.Based on these findings, the developed module was deemed highly feasible. A learning medium is considered highly feasible for use if it achieves a presentation rate between 60-100%. With an average score of 82.39%, the module meets this criterion and can be effectively used in learning.